2008
DOI: 10.1111/j.1365-4632.2008.03627.x
|View full text |Cite
|
Sign up to set email alerts
|

Matrine inhibits invasiveness and metastasis of human malignant melanoma cell line A375 in vitro

Abstract: These findings indicate that matrine inhibits the invasiveness and metastasis of A375 cells in vitro. The mechanisms may be linked to the inhibition of cellular proliferation, induction of apoptosis, and downregulation of heparanase mRNA and protein expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 16 publications
3
40
0
Order By: Relevance
“…HPA-1 has been reported to degrade the extracellular matrix and facilitate the process of the invasion and metastasis of carcinoma (Liu et al, 2008;Yingying et al, 2009;Wagner et al, 2012). A predominant correlation was observed between HPA-1 expression and tumor invasion and lymphatic metastasis in gastric carcinoma (Endo et al, 2001;Takaoka et al, 2003), and this finding is consistent with the results of our study.…”
Section: Discussionsupporting
confidence: 83%
“…HPA-1 has been reported to degrade the extracellular matrix and facilitate the process of the invasion and metastasis of carcinoma (Liu et al, 2008;Yingying et al, 2009;Wagner et al, 2012). A predominant correlation was observed between HPA-1 expression and tumor invasion and lymphatic metastasis in gastric carcinoma (Endo et al, 2001;Takaoka et al, 2003), and this finding is consistent with the results of our study.…”
Section: Discussionsupporting
confidence: 83%
“…Kushen includes matrine, which is an alkaloid with the chemical formula of C 15 H 24 N 20 [5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Matrine has been shown to have a variety of effects in experimental studies, including a inhibitory effect on tumor cells [5,7,9,10,12,13,[16][17][18] and hepatitis [6,15] and a suppression of the proliferation of fibroblasts [8,11,14]. In ophthalmic experimental studies, matrine exhibited anti-inflammatory properties [19], was associated with a reduction in the recurrence rate of pterygia [20] and showed a preventive effect on proliferative vitreoretinopathy [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…As a main alkaloid from Sophora flavescens Ait, matrine (C 15 H 24 N 2 O) also exhibits a variety of biological activities such as anti-inflammation, antivirus, anti-fibrosis, anti-arrhythmia and immunosuppression [7]. Moreover, recent studies have reported that matrine also possesses antitumor activities by inhibiting proliferation and inducing apoptosis against a wide range of cancers, including lung cancer, gastric cancer, breast cancer and so on [8,9,10,11,12,13,14]. Accordingly, our previous study demonstrated that matrine significantly inhibited growth of human nasopharyngeal carcinoma cells in a dose- and time-dependent manner.…”
Section: Introductionmentioning
confidence: 99%